A qualitative exploration of the impact of COVID-19 on food decisions of economically disadvantaged families in Northern Ireland - Eleni Spyreli; Michelle C. McKinley; Jayne V. Woodside; Colette Kelly (BMC, 2021)
Abstract Background The first UK-wide lockdown to prevent the spread of COVID-19 had a serious financial impact on low-income households, a population already in higher risk of food insecurity and poor dietary choices. Qualitative data on the impact of COVID-19 lockdown on food decisions of UK families are scarce. This study aimed to explore how the measures to control the spread of COVID-19 influenced the food-related decisions of socioeconomically deprived families in Northern Ireland. Methods A qualitative study captured data from online individual interviews. Participation was open for parents of children 2-17 years old living on a tight budget in urban and rural areas of Northern Ireland. A sampling matrix enabled equal representation of single- and two-parent households, as well as parents of younger children (<12y) and adolescents (≥12y). Data were collected by using the methods of Photovoice and mapping exercise. Data were analysed through a thematic approach. Results Twelve online interviews were conducted and five distinct themes were identified reflecting families' food-related decisions that were affected by the COVID-19 lockdown: 1) food planning; 2) food purchasing; 3) meal preparation; 4) eating and feeding behaviours and 5) eating food prepared outside the house. Conclusions The restrictions put in place to inhibit the spread of COVID-19 influenced all aspects of dietary decisions of low-income families. Changes observed during this period included frequent consumption of homemade meals, but also increased unhealthy snacking. Infrequent food shopping encouraged good meal planning, but was also a barrier to securing adequate fresh food. Food-related support including school meal assistance contributed to families' food security, particularly those of single parents.